Patient, Public, Consumer, and Community Engagement: From Consucrat to Representative; Comment on "The Rise of the Consucrat" - Matthew DeCamp; Sarah E. Brewer; Vadim Dukhanin (Kerman University of Medical Sciences, 2021)
Patient, public, consumer, and community (P2C2) engagement in healthcare delivery, research, and policy-making has been long considered an ethical obligation and is increasingly a regulatory requirement globally. The requirement to include a P2C2 member on various governing bodies may have inadvertently created what Evelyne de Leeuw calls the "consucrat" - a career consumer who has been designated and professionalized to function on behalf of a particular group or community. The concept of a consucrat can be problematic when a P2C2 member is co-opted by an institution governing body or in situations where institutions only seek and listen to the same voice over time. In this commentary, we suggest that one way to avoid these problems is to take seriously the concept and process of representation. Representation is only meaningful when P2C2 members are actively connected with those whom they represent. Doing so helps ensure P2C2 members remain grounded in the real-world concerns of their constituency and that representatives, backed by the voices of others, will be more powerful in effecting change.